Impact of a Business Educational International Experience Under a Hybrid Program - Pantoja Aguilar, Martin; Arredondo Hidalgo, María Guadalupe (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
This study was conducted on undergraduate students participating in the Global Innovation Scholars (GIS) program between Southern Oregon University (USA) and the University of Guanajuato (Mexico) in the first semester of 2024. The GIS program provides students with a hybrid international experience to learn about international business. Still, it develops in participating students the intercultural skills necessary to perform in a global world. The questionnaire developed qualitatively and quantitatively was focused on detecting the impacts of the course experience on Mexican students, but with an emphasis on the development, or not, of aspects related to intercultural skills. These impacts were measured against Karimova et al.’s model of areas of impact in intercultural learning. Also, results were measured against Neuner’s proposed intercultural skills and competencies needed for global success. The results showed that the GIS Mexican students were impacted positively in all the areas of intercultural learning and developed all the intercultural skills and competencies needed for global success listed by Karimova et al. (2024) and Neuner (2012). It was found that students expressed various aspects of improvement and change in perspective on the business world and the importance of developing intercultural skills for business success. Keywords: Interculturality, business, international